Charting the place of islands in criminology: On isolation, integration and insularity. (November 2021) - Scott, John; Staines, Zoe
In this article, we seek to chart the place of islands in criminology with respect to both their place- and space-based attributes. We explore the possibilities of island criminology through the case of Pitcairn Island, which in 2004 formed the backdrop for a series of sensational sexual assault trials. The trials thrust the Island, its people, history and customs into the international spotlight, acting as a counter-narrative to the popular mythology of islands as idyllic paradises. This case study provides us with an opportunity to re-examine how fundamental concepts for understanding crime and regulation, such as social integration, community and belonging, and exclusion are practised in the often closed and bounded networks of island ecologies.